Designing A Harmonic Leadership Succession In The Berkah Abadi Tekhnik Family Company In Semarang - Rizky Chandra Wisnu Budiawan; Pahlawansjah Harahap; Djoko Santoso (Sean Institute, 2024)
This research aims to explore the design of harmonious leadership succession in family companies using a qualitative case study type approach. The setting of this research is Berkah Abadi Teknik in Semarang. Data collection through observation, in-depth interviews and documentation studies. The data analysis technique reference uses Miles and Huberman's interactive model analysis, including data collection, data condensation, data presentation, verification and drawing conclusions. Through this research, it is known that the planning of harmonious leadership succession in the Berkah Abadi Teknik family company reached the stage where selected successor candidates were involved as heads of business with the first generation of owners playing a role behind the scenes where acceleration was carried out by establishing a company for the development of successor candidates by the first generation of owners, dedication and trust, mentoring and available resources involved by the first generation of owners to uphold family culture is reflected in family values and the sustainability of the family company, the first generation of owners assesses that the successor candidate has met the required criteria. However, it has not been official. The supporting factors are good communication and a sense of belonging, while the inhibiting factors are a succession plan that is less structured and the successor candidate's stamina is drained. The successor candidate plans to place the first generation of owners as supervisors after stepping down so as to avoid conflicts of interest. and the welfare of the pioneer-owners or first generation of owners is guaranteed.